The art of talent management: keys to maximizing performance in the travel industry - Diana Mogrovejo; Jorge Franco-Medina; Alex Pacheco (Cogent Business & Management)
In a sector as dynamic and competitive as tourism, human talent management becomes a key factor. This study was carried out in tourism companies located in Lima, Peru, with the objective of analyzing how human resources strategies employed in areas such as integration, organization, compensation, development, retention and auditing impact the labor productivity of workers. A non-experimental quantitative design with a descriptive and correlational approach was used, collecting data through structured surveys applied to employees in the sector. The study showed that human talent management has a significant impact on labor productivity. Audit was the most highly valued dimension, with 74% of respondents perceiving it at a high level. Compensation was also highlighted as a crucial factor, with 70% of participants considering it essential for employee satisfaction and motivation. In addition, a significant positive correlation was found between staff integration and service quality (r = 0.624, p = 0.001), as well as between professional development and work efficiency (r = 0.710, p = 0.000). Finally, staff organization showed a significant correlation with effectiveness (r = 0.400, p = 0.039). In conclusion, effective talent management practices can be determinant in improving productivity in tourism companies. This study provides valuable empirical evidence that underscores the importance of strategic human resource management to boost job performance in such a demanding environment.